2020
DOI: 10.3390/en13061391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal and Carbon Nanotube Additives on the Thermal Diffusivity of a Silica Gel-Based Adsorption Bed

Abstract: This article presents a study of the effect of metal particle and carbon nanotube additives on the thermal diffusivity of a silica-gel-based adsorption bed of an adsorption chiller. The structural properties of silica gel and carbon nanotubes were investigated using the volumetric method of low-pressure nitrogen adsorption. Thermal characteristic tests of the prepared mixtures based on a silica gel with 5 wt% and 15 wt% of aluminum, copper, or carbon nanotubes were carried out. The obtained results show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 77 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…FTIR measurements, as shown in Figure 7, confirmed that the MWCNTs were not activated [26] within the matrix of silica gel composite [27]. For pristine silica gel, MWCNTs, and MWCNT/SiO 2 composites, the FTIR analysis clearly reveals the structure of the latter.…”
Section: Ftir Measurementsmentioning
confidence: 77%
“…FTIR measurements, as shown in Figure 7, confirmed that the MWCNTs were not activated [26] within the matrix of silica gel composite [27]. For pristine silica gel, MWCNTs, and MWCNT/SiO 2 composites, the FTIR analysis clearly reveals the structure of the latter.…”
Section: Ftir Measurementsmentioning
confidence: 77%
“…Secondly, the intensification of heat exchange can take place by reducing the thermal resistance between the sorbent layer and the heat exchanger, which can be achieved through the use of various types of glues [25]. The heat transfer can also be intensified in the bed itself by adding various materials with high thermal conductivity to it, such as graphite flakes [28], copper, aluminum or carbon nanotubes [29,30].…”
Section: Desalination Technology Electrical Energymentioning
confidence: 99%
“…They observed that the addition of 15 wt.% of aluminum chips significantly improved the silica gel bed's thermal diffusivity. In Kulakowska et al [20], the authors demonstrated a positive effect of the addition of aluminum powder, copper powder, and carbon nanotubes on the thermal diffusivity of the adsorption bed.…”
Section: Introductionmentioning
confidence: 99%